Pemberdayaan Pendidikan Anak Jalanan di Sekolah Master Depok - Rahmanita, Alivia; Rozak, Abdul; Zaharah, Zaharah (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
This study on Child Empowerment of Within Continuing Education at Masters School. This study has the purpose of knowing and investigating in more detail about the Children's Empowerment in Continuing Education at Master Depok School. This research was conducted using qualitative research approach with descriptive analysis methods and data collection techniques used are observation, interviews, and documentation. Data analysis of the Miles and Huberman models including Data Reduction, Data Presentation, and Conclusion Drawing or Verification. In the validity of the data using the technique of the observational and triangulation technique consisting of the technique and source. The results of this study found that street child education in Indonesia was an important issue, therefore Master Depok School in Rejoice to carry out Jalan Children's Empowerment in Continuing Education with several studies by Suharto, namely the level of awareness and desire to change, the level of ability to increase the capacity to obtain access, the level of ability to face obstacles, and solidarity. In the awareness level and desire to change are in teaching and learning activities, participation, swaps and sustainability. Obstacles to educational facilities and a lack of understanding of the transition of the three-learning curriculum to an independent curriculum in empowering can be resolved well together, then the student/i response is positive, they are very happy to be able to go to school again without thinking about educational costs. The building of Master's Depok School can create a chance to study in the street children and grow the spirit to achieve aspirations.